Quantitation of herpes simplex virus type 1 shed in preocular tear film of rabbits treated with acyclovir. - Green, M T (1981)
The quantity and duration of herpes simplex virus type 1 shedding in the preocular tear film of rabbits were measured before, during, and after administration of acyclovir topically, intravenously, and by these routes. Topical administration reduced shedding significantly, Intravenous administration was without effect and in the combination regimen added nothing to the effectiveness of local application. The effects of acyclovir were temporary because there were significant increase in preocular tear film virus shedding after cessation of treatment.